Institutional Transformations of Higher Education: Key Gaps and New Practices. - L. V. Konstantinova; E. S. Titova; A. M. Petrov (Высшее образование в России)
Institutional transformations of higher education in Russia are currently being carried out under the influence of geopolitical factors and a set of gaps between the demands of modern society and the established institutional characteristics of higher education. This article defines the essence of institutional transformations of higher education, systematizes the gaps and contradictions that shape their context in modern Russia, and identifies the main trends in the transformation of the educational and scientific practices of universities that determine the direction of institutional changes. The analysis was conducted using both theoretical and empirical methods, including a content analysis of strategic and reporting documents from 62 leading Russian universities, as well as a secondary analysis of data from the Russian Public Opinion Research Center (VCIOM). It is concluded that the main gap in the institutional transformations of domestic higher education currently lies between trust and value, and the main mechanism is the construction of new practices for educational and scientific activities by universities. The analysis of these practices led the authors to conclude that the direction of institutional changes in the field of educational activities is more associated with the transformation of traditional institutional characteristics, while in the field of scientific activities, it is associated with the formation of new institutional foundations, with a general focus on increasing the integration potential of universities and inter-institutional interaction. The prospects for forming a new national system of higher education are tied to the possibility of consolidating these practices at the systemic level as stable regulatory and organizational characteristics.